2010
DOI: 10.1136/qshc.2009.039511
|View full text |Cite
|
Sign up to set email alerts
|

Organisational culture: variation across hospitals and connection to patient safety climate

Abstract: Hospitals vary in organisational culture, and the type of culture relates to the safety climate within the hospital. In combination with prior studies, these results suggest that a healthcare organisation's culture is a critical factor in the development of its patient safety climate and in the successful implementation of quality improvement initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 29 publications
7
76
1
6
Order By: Relevance
“…The highest values of Pearson's correlation occurred between: Overall HSOPSC and SAQ Safety climate (r=0.69 and p<0.000), Overall HSOPSC and Overall SAQ (r=0.66 and p<0.000), HSOPSC Feedback and communication about error and Overall SAQ (r=0.58 and p<0.000), the HSOPSC (14)(15)(16) .…”
Section: Safety Climate Stress Recognition Perception Of Managementmentioning
confidence: 96%
See 1 more Smart Citation
“…The highest values of Pearson's correlation occurred between: Overall HSOPSC and SAQ Safety climate (r=0.69 and p<0.000), Overall HSOPSC and Overall SAQ (r=0.66 and p<0.000), HSOPSC Feedback and communication about error and Overall SAQ (r=0.58 and p<0.000), the HSOPSC (14)(15)(16) .…”
Section: Safety Climate Stress Recognition Perception Of Managementmentioning
confidence: 96%
“…Furthermore, more bureaucratic organizational cultures are less inclined to carry out quality development than organizations with more equality regarding teamwork (16) .…”
Section: Safety Climate Stress Recognition Perception Of Managementmentioning
confidence: 99%
“…Job satisfaction, the way in which the institution deals with errors, and perception of the types of management by health workers are considered essential indicators of the presence of attitudes that favor a safety climate in health institutions (9)(10) . The current recommendations emphasizes the need for studies that address the individual's behavior within the organization and the indicators of care and quality of care together (11) . The complexity of health care can be even greater when it involves pediatric care units.…”
Section: Introductionmentioning
confidence: 99%
“…Although we asked a single question about team work, the level of agreement with the question was not incomparable to that found in other studies measuring teamwork via a series of questions. 2,3,7,24,25 Our finding could, therefore, be viewed as a good starting point. However, in the current context of emphasising teamwork, particularly given the increasing demands of chronic disease and multimorbidity, and of enhancing the patient experience, it also indicates room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a North American study found variations in the type of hospital organisational culture -some hierarchical and others more oriented towards teamwork -and that the latter culture was more germane to developing a robust patient safety climate. 7 An Australian study of professionals working in different service areas found that specific services had more positive safety cultures, as well as demographic differences in safety attitudes. 2 The most utilised survey tools, such as the 'safety climate survey' and derivatives of this 8 have been deployed in a range of contexts.…”
Section: Introductionmentioning
confidence: 99%